Linkage between Tourism and Climate Change: A Study of the Perceptions of Stakeholders along the Annapurna Trekking Trail - Rayamajhi, Shraddha (Nepal Tourism and Development Review, 2013)
This paper explores the relationship between tourism and climate change. It takes the perceptions of the stakeholders in the tourism sector, mainly the lodge-owners, guides and tourists in the Annapurna Trekking Trail. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7380 Nepal Tourism and Development Review Vol.2(1) 2012 60-86